Proces zmniejszania się użytków rolnych i jego tendencje rozwojowe w południowo-wschodnich województwach Polski (w latach 1960-1970) - Kwiecień, Władysław (Wydział Prawa i Administracji UAM, 1973)
The present paper is devoted to the problems of diminishing of farmland resources as a result of industrial and urban processes. The size and tendencies in the range of diminishing of cultivated area and arable land in Poland in the years 1960 - 1970 have been shown. The problem of lessening of farmland resources as a result of the expansion of industry, building and transport in the south-eastern part of Poland, that is in the districts of Katowice, Kraków, Lublin and Rzeszów, has been presented in detail. In the present paper an argument was presented that a large area of farmland has been excluded from agricultural production as a result of inrational land administration.
The Process of Lessening Farmland Resources and its Developmental Tendencies in the Years 1960 -1970